Correlation between some physical properties for tri-component tellurite glasses and low temperature ultrasonic relaxation - SIDKEY, M. A.; AAL, N.S. Abd El; LATIF, L. Abd El; MONEIM, A. Abd El (Archives of Acoustics, 2001)
Theoretical analysis of ultrasonic wave absorption and elastic moduli for TeO2-V2O5-Sm2O3 glass system is presented. A correlation between low temperature ultrasonic relaxation parameters and other physical (elastic) properties for this glass system was achieved according to a model presented by Bridge and Patel. Correlation coefficients greater than 96% were obtained indicating that correlations between ultrasonic attenuation and activation energy at low temperatures and the bulk modulus of this glass system at room - temperature (through the two crucial structural parameters, number of anions and anion-cation force) exist.